n-Hexane hydroisomerization over Zr-modified bicontinuous lamellar silica mordenite supported Pt as highly selective catalyst: Molecular hydrogen generated protonic acid sites and optimization - M., Ibrahim; A. A., Jalil; W. F. W., Zakaria; N. A. A., Fatah; M. Y. S., Hamid; S. M., Izan; H. D., Setiabudi (Elsevier Ltd, 2021)
Zr-modified bicontinuous lamellar silica mordenite supported Pt catalysts were synthesized using the zirconyl chloride oxahydrate as the precursor for Zr species by the incipient wetness impregnation method. The influence of zirconium loading on the properties of Zr-modified HM@KCC-1 catalysts for n-hexane isomerization were studied. The results of XRD and lattice structure from IR study indicated that increasing zirconium loading did not change the properties of catalysts. The IR study with pre-adsorbed 2,6-dimethylpyridine as a probe molecule affirmed that increasing zirconium loading could increase the Lewis acid sites. The generation of protonic acid sites which were active in n-hexane hydroisomerization was mainly from molecular hydrogen through a hydrogen spill-over mechanism as established by in situ-IR study. The results for the catalytic testing indicated that PtZr/HM@KCC-1 catalyst was highly selective in n-hexane hydroisomerization due to abundant permanent Lewis acid sites for its promotive effect in the generation of protonic acid sites. However, the incorporation of excessive zirconium amount up to 10 wt percent loading led to a decline in the amount of protonic acid sites generated, thus reduced the hydroisomerization performance in the process. The optimum conditions for hydroisomerization of n-hexane over Pt5Zr/HM@KCC-1 were reaction temperature of 293 °C, treatment temperature of 474 °C and F/W of 502 mL/g.min with the predicted value for isomer yield of 83.9%.